Digital maturity of the Russian metallurgical industry: drivers and challenges of growth in new geopolitical conditions. Part II. Key directions of digital transformation - I. S. Prokhorova; V. S. Ustinov; A. V. Elkhova (Вестник университета)
The article continues the research on the prospects of achieving digital maturity in Russian metallurgical industry as one of the digitalization drivers of the Russian economy. The analysis results showed that the metallurgical business has a high innovative potential for the digital maturity growth. The second part examines the application of Industry 4.0 technologies in domestic metallurgy by the example of industry leaders in digitalization.   The purpose study is to determine the directions of digital transformation in metallurgy to achieve digital maturity in new geopolitical conditions based on the innovative activity assessment of industry leaders.   The study object is Russian metallurgical companies (technological development of the industry) drivers.   The study subject is the digital transformation process of metallurgical companies in the conditions of economic sanctions.   The research methodology is based on the innovation activity assessment. The research methods include indicative, comparative, and statistical analyses. The impact of the economic sanctions imposed in 2022 on the digital transformation in the industry has been assessed, problems and approaches to their solution have been identified. The study results demonstrated the significant potential of the metallurgical industry to achieve digital maturity due to the high innovative activity of industry leaders, despite the sanctions. The key areas of digital transformation are digital twins, machine vision and artificial intelligence, the creation of metal products and secondary raw materials marketplaces, which corresponds to the global digitalization trend. This paper is a continuation of the article “The digital maturity of the Russian metallurgical industry: drivers and growth challenges in the new geopolitical environment. Part I. Assessment of the innovation potential of digital transformation”.